1999
DOI: 10.1046/j.1365-2958.1999.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

The response to stationary‐phase stress conditions in Escherichia coli : role and regulation of the glutamic acid decarboxylase system

Abstract: SummaryInducible bacterial amino acid decarboxylases are expressed at the end of active cell division to counteract acidification of the extracellular environment during fermentative growth. It has been proposed that acid resistance in some enteric bacteria strictly relies on a glutamic acid-dependent system. The Escherichia coli chromosome contains distinct genes encoding two biochemically identical isoforms of glutamic acid decarboxylase, GadA and GadB. The gadC gene, located downstream of gadB, has been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
278
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(308 citation statements)
references
References 74 publications
23
278
3
2
Order By: Relevance
“…Highlighting the importance of the AR2 system is the plethora of regulators involved in its regulation, the relative importance of each regulator depending on environmental pH and growth phase. These regulators include: two phosphorelays, EvgAS (Masuda & Church, 2002) and TorRS (Bordi et al, 2003), the stationary phase s s -factor (De Biase et al, 1999), the global regulators Crp ) and H-NS (Hommais et al, 2001), three AraC-like regulators, GadW (Ma et al, 2002), GadX (Shin et al, 2001) and YdeO (Masuda & Church, 2003), and the Era-like GTPase TrmE (Gong et al, 2004). Central to the AR2 system is the activity of the LuxRlike transcription regulator GadE, as most of the regulators listed target gadE expression.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighting the importance of the AR2 system is the plethora of regulators involved in its regulation, the relative importance of each regulator depending on environmental pH and growth phase. These regulators include: two phosphorelays, EvgAS (Masuda & Church, 2002) and TorRS (Bordi et al, 2003), the stationary phase s s -factor (De Biase et al, 1999), the global regulators Crp ) and H-NS (Hommais et al, 2001), three AraC-like regulators, GadW (Ma et al, 2002), GadX (Shin et al, 2001) and YdeO (Masuda & Church, 2003), and the Era-like GTPase TrmE (Gong et al, 2004). Central to the AR2 system is the activity of the LuxRlike transcription regulator GadE, as most of the regulators listed target gadE expression.…”
Section: Introductionmentioning
confidence: 99%
“…The glutamate decarboxylase (GAD, 1 EC 4.1.1.15) system has been extensively studied because of its major role in the acid resistance of enteric pathogens such as E. coli O157, Shigella flexneri, and Listeria monocytogenes (6,7,8,29). E. coli contains two genes, gadA and gadB (mapped at 78 and 33 min on its chromosome), which encode two biochemically indistinguishable forms of GAD and are very similar in sequence (2,9,24).…”
mentioning
confidence: 99%
“…E. coli contains two genes, gadA and gadB (mapped at 78 and 33 min on its chromosome), which encode two biochemically indistinguishable forms of GAD and are very similar in sequence (2,9,24). Sequential reaction through GAD and the putative glutamate/GABA antiporter encoded by the gadC gene allows cells to remove intracellular protons (8).…”
mentioning
confidence: 99%
“…32,33 One of the most efficient acid resistance systems in E. coli, the Gad system, is based on the coordinated action of two isoforms of glutamate decarboxylase (GadA and GadB) and of a specific glutamate/g-aminobutyrate (GABA) antiporter (GadC). 34,35 The gadA/BC genes, activated in response to acid stress, are subject to complex circuits of regulation involving the AraC-XylS family regulator YdeO. 36 In this study, we demonstrate that YdeO contributes to the multi-drug resistance as well as the acid resistance of E. coli.…”
Section: Introductionmentioning
confidence: 66%
“…One very efficient E. coli acid resistance system encompasses two isoforms of glutamate decarboxylase (gadA and gadB) and a putative glutamate/GABA antiporter (gadC). 34,35 It is subject to complex controls that vary with growth medium, growth phase and growth pH. Earlier work has revealed that this system is also controlled by YdeO (Figure 4).…”
Section: Discussionmentioning
confidence: 99%